Seasonal effects on urinary iodine concentrations in women of reproductive age: An observational study in Tanzania and South Africa. Issue 1 (28th October 2021) - Arns-Glaser, Leonie; Zandberg, Lizelle; Assey, Vincent D; Baumgartner, Jeannine; Abdallah, Fatma; Galetti, Valeria; Dary, Omar; Zimmermann, Michael B; Andersson, Maria
ABSTRACT: Background: Iodine intake in populations is usually assessed by measuring urinary iodine concentrations (UICs) in spot samples. Hot climate conditions may reduce urine volume, thus leading to overestimations of UIC and thereby masking inadequate iodine intake. Objectives: We investigated the effects of season on UICs in 2 populations exposed to high-temperature climates. Methods: In this observational study, we examined women (18–49 years) in Tanzania ( n cold  = 206; n hot  = 179) and South Africa ( n cold  = 157; n hot  = 126) during cold and hot seasons. From each woman in both seasons, we obtained two 24-hour urine collections and 2 spot urine samples, as well as salt, water, and cow's milk samples. We measured the urine volume, UIC, and urinary creatinine concentration (UCC). The 24-hour urinary iodine excretion (UIE) was calculated and used to estimate the iodine intake. We used linear mixed-effects models to test for differences between seasons. Results: In Tanzanian women, we observed no seasonal effect on the urine volume, 24-hour UIE, 24-hour UIC, spot UIC, spot UIC:UCC ratio, or salt iodine concentration. In South African women, the median 24-hour urine volume was 1.40 L (IQR, 0.96–2.05 L) in the winter and 15% lower in the summer ( P  < 0.001). The median 24-hour UIE was 184 µg/day (IQR, 109–267 µg/day) in the winter and 34% lower in the summer ( P  < 0.001), indicating a lower iodine intake. As a result, UICs did not significantly differ between seasons in 24-hour collections and spot samples, whereas the spot UIC:UCC ratio differed by 21% ( P  < 0.001) and reflected the lower iodine intake. In both study populations, the within- and between-person variabilities in urine volume, 24-hour UICs, and spot UICs were higher than the variability between seasons. Conclusions: Spot UIC may slightly overestimate the iodine intake in hot temperatures due to concentrated urine, and methods to correct for urine volume may be considered. Local seasonal differences in iodine intakes may also occur in some populations. This trial was registered at http://www.clinicaltrials.gov as NCT03215680.